Comparación de tres ecuaciones alométricas para estimar la biomasa arbórea para su valoración económicas del secuestro de co2, en un bosque de colina baja del Distrito de Torres Causana, Loreto, 2022 - López Mori, José Luis (2024)
In a low hill forest in the district of Torres Causana, Loreto, Peru, a comparison of three allometric models was carried out to estimate tree biomass for the economic evaluation of CO2 sequestration. Information from forest concession 16-LOR MAR/CON-MAD-2016-035 of the operational plan N° 01 (PC N° 19) of forest concessions for timber purposes was used. The results show that 2760 trees of 34 forest species, 30 genera and 14 botanical families have been recorded. The allometric equation of Higuchi and Carvalho (1994), with R2 = 0.88 and SEE 16.38%, was the most adequate to estimate the individual biomass per tree. The total biomass was 249 360.53 kg/ha, with the largest contributions from the Fabaceae family, with 89 006.48 kg/ha, and the Lauraceae family, with 50 104.72 kg/ha. The economic value of CO2 sequestration is 37 493.82 USD/ha; Fabaceae and Lauraceae contribute 13 383.01 USD/ha and 7533.74 USD/ha, respectively. According to the statistics, there is a great disparity between families in terms of the average economic value of the environmental service of CO2 sequestration.